Peran Kompetensi Sumber Daya Manusia UMKM Dalam Meningkatkan Kinerja Umkm Desa Pujorahayu Kec. Negeri Katon Pesawaran - Helmita Helmita; Naim Naim (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2023)
The role of Human Resources of Micro, Small and Medium Enterprises competence is very important in improving the performance of Micro, Small and Medium Enterprises. This study aims to: find out the role of Human Resources for Micro, Small and Medium Enterprises, find out the driving factors for improving the performance of Micro, Small and Medium Enterprises; and find the inhibiting factors in improving the performance of Micro, Small and Medium Enterprises in Pujorahayu village. This study is a qualitative descriptive study. The subjects of this study were Micro, Small and Medium Enterprises Owners, employees of Micro, Small and Medium Enterprises and customers who selected by purposive sampling techniques. Data collection techniques used interview, observation and literature studies. Data analysis techniques used qualitative descriptive analysis. The result shows that: the role of Human Resources for Micro, Small and Medium Enterprises competence is needed who have good abilities and skill, so it requires special training for employees of Micro, Small and Medium Enterprises. Besides Micro, Small and Medium Enterprises owners, the government and related agencies also participate in training the Human Resources for Micro, Small and Medium Enterprises competence to improve the performance of Micro, Small and Medium Enterprise.